Fintech and SMEs sustainable business models: reflections and considerations for a circular economy - Pizzi, Simone (2022)
Following the operational paradigms proposed by Industry 4.0, the last years have been characterized by the rapid growth of technology-based firms increasingly adopting sustainable business models. In particular, an increasing number of Fintech enterprises have started to launch new services in order to avoid the organizational barriers that impact negatively on the voluntary adoption of sustainable business models by SMEs. However, research is still scarce in systematizing the efforts and identifying the facilitating factors for such a transition. Drawing on a diverse set of companies, case studies linking Fintech application and circular economy (CE) in diverse industries and contexts are analyzed and discussed. The findings of the qualitative analysis suggest that Fintech, an example of sectors developed under the influence of Industry 4.0, can play a relevant role in the transition of SMEs toward a more sustainable business model leading to better integration of circular economy practices. A conceptual framework using the ReSOLVE model is then presented with relevant implications for both research and practice.